Penggunaan Daun Ubi Kayu (Manihot esculenta) dengan Pengolahan Berbeda terhadap Blood Urea Nitrogen Kambing Peranakan Etawa Jantan - Okni Winda Artanti; Silvia Andriani (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2020)
The objective of this experiment was to evaluate the effect of fresh, dried or silage cassava leaf to the blood urea nitrogen (BUN) of male Etawa Crossbreed (EC) goats. Twelve EC goats (grouping based on body weight with a weight range K1: 19-20 kg; K2: 20-21 kg; K3: 21-22 kg; K4: 22 kg) were allocated in housed individually throughout 90-day trial duration (14 days for animal's adaptation to the experimental diets and 7 days of faeces collection). Experimental design was randomized complete block design consisted of 3 treatments and 4 replications: concentrate + fresh cassava leaf (P0); concentrate + dried cassava leaf (P1); and concentrate + silage cassava leaf (P2). Concentrat was given at level of 50% (3% BW) and forage was given ad libitum respectively for each treatments. Variables observed were crude fiber intake, crude fiber digestibility, crude protein digestibility and blood urea nitrogen (BUN). Data were analyzed using analysis of variance (ANOVA), if there were significant effect of treatments were continued using duncan multiple range test. The results of this experiment showed that the processing of cassava leaves increased on crude fiber intake, crude fiber and crude protein digestibibility, but did not effect on blood urea nitrogen (BUN). In conclusion, processing of cassava leaves improved the consumption, digestibility but did not effect on blood urea nitrogen (BUN) of EC goats. Keywords: Blood Urea Nitrogen, Cassava Leaf, Male Etawa Crossbreed Goat